The British-American Colonies' Relationships with the Crown and Pedagogical Implications in British and American Literature for English Language Teaching - Zounhin Toboula, Coffi Martinien; Seguedeme, Hergie Alexis; Aguessy, Anne Nathalie Jouvencia Agossi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
This study looks at the historical and current relationships between the British Empire and its former American colonies, now the US, through British literature. It covers the colonial period from early exploration and settlement to the struggle for independence with a focus on the American Revolutionary War (1775-1783). It examines how British colonial policies, and taxation without representation, contributed to the tensions that led to the war. Through a close analysis, this study looks at the political, economic, and cultural factors that shaped the relationship between Britain and its colonies. It also investigates the impact of these historical events on British literature, power, resistance, and identity. The study also explores how these literary representations of colonial relations can be used in language teaching to deepen learners' understanding of historical context and its effect on literary expression. By combining historical analysis with literary study this research shows the pedagogical value of teaching colonial history in the context of British literature, especially for language learners who want to understand the cultural and historical background of the English language.